2010
DOI: 10.1111/j.1751-9004.2010.00325.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Fit, Processing Fluency, and Narrative Persuasion

Abstract: For millennia, people have used narratives to inform and persuade. However, little social psychological research addresses how and when narrative persuasion occurs, perhaps because narratives are complex stimuli that are difficult to vary without significantly changing the plot or characters. Existing research suggests that regulatory fit and/or processing fluency can be varied easily and in ways completely exterior to narrative content but that nonetheless affect how much narratives engage, transport, and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 61 publications
(143 reference statements)
0
31
1
Order By: Relevance
“…In spite of a strong relationship between transportation and enjoyment and their common co-occurrence (Green et al, 2008;Vaughn et al, 2010), our study did not uncover any moderated effects on transportation, despite revealing moderated effects on enjoyment. One possible explanation is that although need for affect correlates with transportation (Appel & Richter, 2010), and uncertainty appears to contribute to arousal and subsequent enjoyment for those high on need for affect, it may not be as necessary for the experience of transportation.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In spite of a strong relationship between transportation and enjoyment and their common co-occurrence (Green et al, 2008;Vaughn et al, 2010), our study did not uncover any moderated effects on transportation, despite revealing moderated effects on enjoyment. One possible explanation is that although need for affect correlates with transportation (Appel & Richter, 2010), and uncertainty appears to contribute to arousal and subsequent enjoyment for those high on need for affect, it may not be as necessary for the experience of transportation.…”
Section: Discussioncontrasting
confidence: 99%
“…The importance of processing fluency in predicting how spoilers influence enjoyment was shown by Leavitt and Christenfeld (2013), who found that knowing the outcome of a story in advance increased the perceived ease of reading, which in turn had a positive effect on their enjoyment measure. In addition, processing fluency increases transportation, which positively impacts enjoyment (Vaughn, Childs, Maschinski, Niño, & Ellsworth, 2010). Hence, ease of processing (whether as the result of knowing the outcome of the story or due to something else) will lead to greater transportation and enjoyment (cf.…”
Section: Need For Cognitionmentioning
confidence: 99%
“…Familiarity also has a positive impact on transportation, possibly due to increased processing fluency (Green et al, 2008;Vaughn et al, 2010). Rosenbaum and Johnson (2016) found that more frequent fiction readers had negative responses to spoilers for short stories, yet Leavitt and Christenfeld (2013) found no support for this interaction.…”
Section: Involvementmentioning
confidence: 93%
“…Factors such as people's prior experiences and expectations can aid processing fluency, producing more positive evaluations of the information or experience (Reber, Schwarz, & Winkielman, 2004). Processing fluency has also been linked to increased narrative transportation (Vaughn, Childs, Maschinski, Niño, & Ellsworth, 2010). Winkielman and Cacioppo (2001) described a "hedonic fluency model," which claims that people prefer "average, prototypical, or symmetrical" (p. 992) information that they can easily process, because this confirms their view of the world is adequate.…”
Section: Processing Fluencymentioning
confidence: 99%
“…NOTE 1. Although it is possible that an individual's interest in a particular narrative can lead to greater immersion into that narrative, studies on processing fluency suggest an alternative possibility: that a story matching a reader's pre-reading mood can lead to greater transportation (e.g., sad readers may be more easily transported into sad stories; Green et al, 2012;Vaughn, Childs, Maschinski, Niño, & Ellsworth, 2010). Ironically, it may be harder to become transported into a story that one chooses to change one's mood, at least initially, because the emotional mismatch may impede feelings of ease or fluency.…”
Section: Future Research Directionsmentioning
confidence: 98%